UNDERPINNING, TYPES; METHODS; TECHNIQUES AND MITIGATION; A CASE STUDY OF A (G+3) RESIDENTIAL BUILDING ANALYSIS AND DESIGN - Muazzam Nawaz; Abdul Munam (Spectrum of Engineering Sciences, 2025)
UNDERPINNING, TYPES; METHODS; TECHNIQUES AND MITIGATION; A CASE STUDY OF A (G+3) RESIDENTIAL BUILDING ANALYSIS AND DESIGN